Leveraging high-level petri nets for cyber-physical systems development - Fernandes, Nuno (2024)
Petri nets are a powerful graphical formalism that is well-suited for modeling and simulating concurrent systems. However, existing solutions for integrating high-level Petri net models with external systems and physical devices are limited, restricting their applicability for developing cyber-physical systems. This paper presents a middleware implementation that bridges this gap by enabling reference nets, a high-level Petri net class supported by the Renew tool, to interface with physical devices. The proposed middleware implementation facilitates Petri net-driven development, where the graphical net model serves as the core specification driving the system’s behavior using a low-code, top-down approach. This approach transforms the traditionally autonomous Petri net model into an event-driven, reactive model capable of bidirectional communication with external physical components. The paper demonstrates the middleware’s usage through a case study involving a gate and button as physical devices, exemplifying how their states and events can be seamlessly integrated into the high-level Petri net model’s execution semantics. This integration empowers the development of sophisticated cyber-physical systems with Petri nets as the central, formal modeling paradigm.